Proceso de construcción de liderazgo en dirigentes de las federaciones indígenas participantes en la organización de pueblos afectados por la actividad petrolera, Iquitos 2022 - Musoline Acho, Joel (2024)
The present research “Process of leadership construction in leaders of the indigenous federations participating in the “organization of Peoples Affected by Oil Activity”, Iquitos 2022. Its objective was to understand and describe the process of leadership construction of leaders of the indigenous federations. that participate in the organization of Peoples Affected by Oil Activity, and as specific objectives: a) Describe the behaviors adopted by the indigenous leaders participating in the organization of the PAAP, b) Identify the discourses and practices in relation to the indigenous leadership that They are built from participation in the PAAP organization, and c) Know the perception of indigenous leaders regarding the construction of their leadership in the PAAP organization. The research had a qualitative approach, descriptive level, ethnographic design, the study population was 40 leaders belonging to the PAAP; Interviews and direct observation were applied as techniques. As a result, it was obtained that the indigenous populations located in the oil zones of Loreto, present poverty indicators, facing the lack of access to basic services, therefore, they organize with the purpose of asserting and respecting their rights, a space where it is seen the leadership of the leaders representing the communities, federations and organizations that are affected by oil activity. Likewise, the role and capacity of the indigenous leader is important in times of resolving internal and external conflicts that seek communal benefit